Incorporating mechanical strain in organs-on-a-chip: Lung and skin - Guenat, Olivier T.; Berthiaume, François (Biomicrofluidics, 2018)
In the last decade, the advent of microfabrication and microfluidics and an increased interest in cellular mechanobiology have triggered the development of novel microfluidic-based platforms. They aim to incorporate the mechanical strain environment that acts upon tissues and in-vivo barriers of the human body. This article reviews those platforms, highlighting the different strains applied, and the actuation mechanisms and provides representative applications. A focus is placed on the skin and the lung barriers as examples, with a section that discusses the signaling pathways involved in the epithelium and the connective tissues.